Comparison of the methods for isolation and detection of SARS-CoV-2 RNA in municipal wastewater - Lucansky, Vincent; Samec, Marek; Burjanivova, Tatiana; Lukacova, Eva; Kolkova, Zuzana; Holubekova, Veronika; Turyova, Eva; Hornakova, Andrea; Zaborsky, Tibor; Podlesniy, Petar; Reizigova, Lenka; Dankova, Zuzana; et al. (Frontiers in Public Health, 2023)
Coronavirus SARS-Cov-2 is a causative agent responsible for the current global pandemic situation known as COVID-19. Clinical manifestations of the disease include a wide range of symptoms from mild (i.e., cough, fever, dyspnea) to severe pneumonia-like respiratory symptoms. It has been shown that SARS-Cov-2 could be detected in the stool of COVID-19 patients. Waste-based epidemiology (WBE) has been shown as a promising approach to early detection and monitoring of SARS-CoV-2 in the local population via collection, isolation, and detection of viral pathogens from environmental sources. The aim of our study was to 1) select the optimal protocol for monitoring the epidemiological situation in region Turiec, Slovakia; 2) compare methods for SARS-CoV-2 separation and isolation, including virus precipitation by polyethylene glycol (PEG), virus purification via ultrafiltration (Vivaspin®), and subsequent isolation by NucleoSpin RNA Virus kit (Macherey-Nagel) and direct isolation from wastewater (Zymo Environ Water RNA Kit); 3) evaluate the impact of water freezing as well as 4) the role of wastewater filtration on virus stability; 5) determinate appropriate methods including digital droplet PCR (RT-ddPCR) and RT-qPCR (targeting the same genes, i.e., RdRp and gene E) for quantitative detection of SARS-CoV-2 in wastewater samples. The outcomes of our study suggest that WBE is a valuable early warning alert and represent a non-invasive approach for monitoring viral pathogens and, thus, protecting public health on a regional and national scale.